2016
DOI: 10.1371/journal.pone.0153464
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Periodontitis and Incident Type 2 Diabetes among Male Workers from a 5-Year Follow-Up to MY Health Up Study

Abstract: AimsThe purpose of this study was to examine whether periodontitis is associated with incident type 2 diabetes in a Japanese male worker cohort.MethodsThe study participants were Japanese men, aged 36–55 years, without diabetes. Data were extracted from the MY Health Up study, consisting of self-administered questionnaire surveys at baseline and following annual health examinations for an insurance company in Japan. The oral health status of the participants was classified by two self-reported indicators: (1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 31 publications
(49 reference statements)
1
25
2
3
Order By: Relevance
“…Figure 1 showed the searching and including process. Appendix Table S1 and S2 summarized the characteristics of 43 cross-sectional studies and 12 [62,23,[63][64][65][66][67][68]39,[69][70][71] cohort studies, respectively. All included cross-sectional studies and cohort studies were scored more than 3.…”
Section: Results Of Search and Characteristics Of Included Studiesmentioning
confidence: 99%
“…Figure 1 showed the searching and including process. Appendix Table S1 and S2 summarized the characteristics of 43 cross-sectional studies and 12 [62,23,[63][64][65][66][67][68]39,[69][70][71] cohort studies, respectively. All included cross-sectional studies and cohort studies were scored more than 3.…”
Section: Results Of Search and Characteristics Of Included Studiesmentioning
confidence: 99%
“…Very few prospective cohort studies have shown positive associations of baseline periodontitis with incident type 2 diabetes (Miyawaki et al, 2016; Chiu et al, 2015; Demmer et al, 2008). However, two recent reviews of clinical trials assessing the effect of periodontitis treatment on HbA1c levels among subjects with type 2 diabetes showed very modest reductions (Li et al, 2015; Simpson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews of epidemiologic studies suggest a bidirectional association between type 2 diabetes and periodontitis (Borgnakke et al 2013). Very few prospective cohort studies have shown positive associations of baseline periodontitis with incident type 2 diabetes (Demmer et al 2008, Chiu et al 2015, Miyawaki et al 2016). However, two recent reviews of clinical trials assessing the effect of periodontitis treatment on HbA1c levels among subjects with type 2 diabetes showed very modest reductions (Li et al 2015, Simpson et al 2015.…”
mentioning
confidence: 99%
“…One study found only a tendency for increased risk (Ide et al 2011 concluded that there was "scant evidence" for periodontitis promoting the development of T2DM and recommended further studies in different populations. A more recent search of the literature reveals only a small number of further studies investigating periodontitis (Chiu et al 2015, Miyawaki et al 2016, or tooth loss (Liljestrand et al 2015) as risk factors for incident T2DM.…”
mentioning
confidence: 99%